Optimasi formula plasticizer gliserol dan filler carboxymethyl cellulose terhadap kekuatan mekanik pada biodegradable film packaging berbasis pati singkong - Siti Munfarida; Amalia Nur Kumalaningrum; Nita Ariestiana Putri; Jefri Pandu Hidayat; Rizka Ayu Yuniar; Lasma Barbara Naibaho (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
The use of conventional plastics, which are difficult to degrade, has caused serious environmental problems, necessitating alternatives in the form of biodegradable plastics (bioplastics). Biofilms are anticipated to address social issues in line with the 12th SDG goal, namely the management and reduction of packaging waste generated daily. By utilizing abundant local cassava starch, the produced biofilms are anticipated to possess good mechanical properties and low water absorption, making them a potential eco-friendly alternative for food packaging while supporting the use of local resources. This study aims to develop cassava starch-based biofilms as environmentally friendly packaging by optimizing the formulation of carboxymethyl cellulose (CMC) and glycerol. The research employs cassava starch as the primary matrix, CMC as a filler to enhance mechanical properties, and glycerol as a plasticizer to improve the flexibility of the biofilm. The research methods include cassava starch extraction, mixing of materials with stirring and heating, and drying the gel into a biofilm. The biofilm's characteristics were analyzed through tensile strength and elongation tests. The results showed that the formula with a cassava starch concentration of 15 grams, 1% CMC, and 6% glycerol yielded the highest tensile strength value of 1.56 MPa, meeting the Japanese Industrial Standard (JIS) for edible films (≥ 0.392 MPa). The best elongation value reached 199.6%, demonstrating excellent flexibility according to JIS and Indonesian National Standards (SNI). This study indicates that the appropriate combination and concentration of materials can produce biofilms with the potential to replace conventional plastics, support environmental sustainability, and optimally utilize local resources